Investigation of the antiarrhythmic mechanism of the multi-herbal medicine Xing Su Ning - Ma, Y; Wilkins, R; Ellory, C; Vaughan-Jones, R; Mao, P; Zhao, Z; Zhang, X; Jiang, J (Australasian Society of Clinical and Experimental Pharmacologists and Toxicologists and The British Pharmacological Society, 2015)
Introduction. Xing Su Ning (XSN) is a multi-herbal Chinese medicine produced by Momentum Pharmaceutical Co. Ltd., which is sold in China since 2005 for treating cardiac ventricular arrhythmia, especially arrhythmias induced by cardiac ischemia and viral myocarditis. Aims. To discover the cellular electrophysiological mechanism of the actions of XSN in treating cardiac arrhythmia. Methods. Whole-cell patch-clamp techniques (1) were used to record action potentials and whole cell current in isolated adult rat ventricular myocytes. The myocytes were continuously perfused with physiological solution without or with XSN. Results. XSN at 2mg/ml significantly prolonged the action potential Duration (APD) as shown in the Figure: control was 45.4ms±4.9 and with XSN 2mg/ml was 52.2ms±4.5 (P<0.01, n=7). At this concentration XSN did not have significant effect on the resting potential or the amplitude of the action potential. The effect of XSN is reversible upon the washout of the medicine. Discussion. XSN Prolongs APD, an action that increases the effective refractory period which suppress tachyarrhythmias caused by reentry mechanisms. XSN displays the property of Class III antiarrhythmic drugs, such as amiodarone, without adverse reactions. Further studies on the effect of XSN at various concentrations on action potential and ionic channels, i.e. potassium channels, will be carried out. (1) Ma Y-L et al (2006) European Journal of Pharmacology. 545:87-92 2 4 6 8 10 46 48 50 52 54 b aandc a-Control b-XSN 2mg/ml c-Recovery 20mV 20ms XSN 2mg/ml Action Potential Duration (ms) Time (Min)